Respostas
respondido por:
1
Boa tarde
2^(x+1) + 2^x = 48
2*2^x + 2^x = 48
3*2^x = 48
2^x = 48/3 = 16 = 2^4
x = 4
2^(x+1) + 2^x = 48
2*2^x + 2^x = 48
3*2^x = 48
2^x = 48/3 = 16 = 2^4
x = 4
edllaketoll:
muito obrigada!
respondido por:
1
É só chamar 2× de y ,por exemplo, e substituir depois
2×.2+2×=48
2×=y
y2+y=48 ,ou melhor, 2y+y=48
3y=48
y=16
2×=y
2×=16
2×=2^4
x=4
2×.2+2×=48
2×=y
y2+y=48 ,ou melhor, 2y+y=48
3y=48
y=16
2×=y
2×=16
2×=2^4
x=4
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás